2021
DOI: 10.1002/glia.24017
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial Cx30 differentially impacts synaptic activity from hippocampal principal cells and interneurons

Abstract: Astrocytes play important roles in brain function via dynamic structural and functional interactions with neurons. Yet the underlying mechanisms remain poorly defined. A typical feature of astrocytes is the high expression of connexins, which mediate their extensive intercellular communication and regulate their structural properties. In particular, connexin 30 (Cx30), one of the two connexins abundantly expressed by astrocytes, was recently shown to be a critical regulator of excitatory synaptic transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The close contact of astrocytic branches with synapses allows astrocytes to sense neuronal activity via their ion channels and neurotransmitter receptors ( Ventura and Harris, 1999 ). Disruption of astrocytic networks, for example, by inactivation of connexin43 and connexin30 reduced synaptic transmission ( Perea et al, 2009 ; Giaume et al, 2010 ; Pannasch et al, 2011 ; Pereda, 2014 ; Charvériat et al, 2017 ; Hardy et al, 2021 ). Accordingly, connexin30 and astrocyte-targeted connexin43 knock-out mice as well as connexin43 and connexin30 double knock-out mice display impaired performance in sensorimotor and spatial memory tasks ( Theis et al, 2003 ; Lutz et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The close contact of astrocytic branches with synapses allows astrocytes to sense neuronal activity via their ion channels and neurotransmitter receptors ( Ventura and Harris, 1999 ). Disruption of astrocytic networks, for example, by inactivation of connexin43 and connexin30 reduced synaptic transmission ( Perea et al, 2009 ; Giaume et al, 2010 ; Pannasch et al, 2011 ; Pereda, 2014 ; Charvériat et al, 2017 ; Hardy et al, 2021 ). Accordingly, connexin30 and astrocyte-targeted connexin43 knock-out mice as well as connexin43 and connexin30 double knock-out mice display impaired performance in sensorimotor and spatial memory tasks ( Theis et al, 2003 ; Lutz et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, it has already been shown that hippocampal Cx30 protein levels, as well as astrocytic network size, can be modulated by neuronal activity [ 18 , 37 ], suggesting that there is a close relationship between astrocytic network size and the activation of underlying neuronal networks. However, this modulation is complex, as it differentially impacts the principal cells and the interneurons [ 23 ]. In addition, Cx30 can also act via other mechanisms, such as signaling and protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of action potentials evoked by depolarizing pulses was lower in CA1 pyramidal cells from AAV-GFAP-Cx30-injected mice (Fig 5C). Previous work on mice deficient for astroglial connexins reported a decrease in the amplitude and duration of CA1 pyramidal cells afterhyperpolarization (AHP) [23][24][25], i.e., the refractory period following action potential discharges during which neuron membrane potential is hyperpolarized (undershoot). We thus investigated AHP in mice with upregulated Cx30 and found an increased amplitude (approximately 40%) and duration (approximately 15%).…”
Section: Astroglial Cx30 Enhanced Expression Impairs Ca1 Pyramidal Ce...mentioning
confidence: 99%
“…The close contact of astrocytic branches with synapses allows astrocytes to sense neuronal activity via their ion channels and neurotransmitter receptors (Ventura and Harris, 1999). Disruption of astrocytic networks for example by inactivation of connexin43 and 30 reduced synaptic transmission (Charvériat et al, 2017; Giaume et al, 2010; Hardy et al, 2021; Pannasch et al, 2011; Perea et al, 2009; Pereda, 2014). Accordingly, connexin30 and astrocyte-targeted connexin43 knockout mice as well as connexin43 and 30 double knockout mice display impaired performance in sensorimotor and spatial memory tasks (Lutz et al, 2009; Theis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%